THE ROLE OF EMPLOYEE TRAINING AND DEVELOPMENT IN ACHIEVING ORGANISATIONAL OBJECTIVES: A STUDY OF ACCRA TECHNICAL UNIVERSITY - churchill, ransford quarmyne (Archives of Business Research, 2018)
Training and development is the field which is concerned with organizational activity aimed at bettering the performance of Individuals and groups in organizational setting and to achieve the set objectives of the organization. It is a combined role often called human resources development meaning the development of “Human” resources to remain competitive in the marketplace in achieving objectives. Training focuses on doing activities today to develop employees for their current jobs and development is preparing employees for future roles and responsibilities. It carries out an analysis that the objective of training and development is to creative learning organizations which ensure that employees through value addition can effectively perform their jobs, gains competitive advantage and seek self-growth: this measurable performance resulting from good training and development, shall enhance organization development. It is a process transferring information and knowledge to employers. It is equipping employers to translate that information and knowledge into practice with a view to enhancing organization effectiveness and productivity, and the quality of a management of people. It should be considered along with education policies and systems which are crucial to the development of human resources.